2021
DOI: 10.1002/slct.202101709
|View full text |Cite
|
Sign up to set email alerts
|

Oxamide Derivatives as Potent α‐Glucosidase Inhibitors: Design, Synthesis, In Vitro Inhibitory Screening and In Silico Docking Studies

Abstract: Diabetes mellitus (DM) is a well‐known progressive endocrine disorder and has become a serious worldwide medical concern stimulating the search for new therapeutic agents. In the current study, nitrogen and oxygen based twenty oxamide derivatives were synthesized and their potential to inhibit α‐glucosidase enzyme was studied. Oxamides were synthesized using oxalyl chloride and corresponding aniline in 1 : 2 ratio in basic medium. Structures of these compounds were determined by mass spectrometry, various spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Given that many oxalamide compounds are biologically and pharmaceutically active [34][35][36][37][38][39][40][41][42][43][44][45], their effect on the metabolic activity of mammalian cells was evaluated. The effect of these compounds on the metabolism of bone marrow-derived mast cells (BMMCs) was evaluated using the XTT assay which measures the nicotinamide adenine dinucleotide phosphate (NADPH)-dependent bioreductase activity of live cells, a key mitochondrial process necessary for energy generation.…”
Section: Cell Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that many oxalamide compounds are biologically and pharmaceutically active [34][35][36][37][38][39][40][41][42][43][44][45], their effect on the metabolic activity of mammalian cells was evaluated. The effect of these compounds on the metabolism of bone marrow-derived mast cells (BMMCs) was evaluated using the XTT assay which measures the nicotinamide adenine dinucleotide phosphate (NADPH)-dependent bioreductase activity of live cells, a key mitochondrial process necessary for energy generation.…”
Section: Cell Metabolismmentioning
confidence: 99%
“…Oxalamide compounds are of considerable interest due to their potential in biomedical applications [34][35][36][37][38][39][40][41][42][43][44][45], catalysis [46][47][48], foods [49], and self-assembling behavior to form gels [50][51][52][53][54][55][56]. The oxalamide functional group consists of two amide groups next to each other in reverse mode, connected by two consecutive carbonyl groups, which has been extensively used as supramolecular synthon to generate LMWGs [50][51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…Nine out of twenty compounds were found to exhibit strong inhibition potential in the range of IC 50 = 38.2-75.8 μM. [29]…”
Section: α-Glucosidase Inhibition Of Oxamide Ligandsmentioning
confidence: 97%
“…Oxamides O1-O20 were scanned against α-glucosidase enzyme and the resultant data is already reported by our group previously. [29] DNJ (1-deoxynojirimycin) was used as a standard inhibitor. The inhibitory study showed that all tested compounds exhibited modest inhibition potential (IC 50 ranges in between 38.2-390.8 μM) with standard DNJ (IC 50 = 425.6 � 1.3 μM).…”
Section: α-Glucosidase Inhibition Of Oxamide Ligandsmentioning
confidence: 99%
See 1 more Smart Citation